2023
DOI: 10.3390/microorganisms11030645
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antibacterial Proficiency of Green Bioformulated Zinc Oxide Nanoparticles with Potential Fosfomycin Synergism against Nosocomial Bacterial Pathogens

Abstract: The drug resistance of bacterial pathogens causes considerable morbidity and death globally, hence there is a crucial necessity for the development of effective antibacterial medicines to address the antibacterial resistance issue. The bioprepared zinc oxide nanoparticles (ZnO-NPs) were prepared utilizing the flower extract of Hibiscus sabdariffa and then characterized using different physicochemical techniques. The antibacterial effectiveness of the bioprepared ZnO-NPs and their synergism with fosfomycin were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Portulaca oleracea leaf extract-mediated ZnO NPs were reported by Gherbi et al [29] to display an indirect bandgap of 2.15-2.74 eV and direct bandgap of 2.97-3.91 eV. Similarly, other literature studies reported a bandgap of 3.21 eV from Hagenia abyssinica leaf extracts [31], 3.8 eV from Hibiscus sabdariffa flower extract [32], and 3.3 eV from Cnidoscolus aconitifolius aqueous leaf extracts [33]. Such differences of bandgap variations could emanate from several factors, ranging from the material particle size and surface roughness to the effect of lattice strain among the ZnO NPs formed from different plant extracts [34].…”
Section: Characterization Of Tm@zno/tmc Nc Hydrogelmentioning
confidence: 83%
See 1 more Smart Citation
“…Portulaca oleracea leaf extract-mediated ZnO NPs were reported by Gherbi et al [29] to display an indirect bandgap of 2.15-2.74 eV and direct bandgap of 2.97-3.91 eV. Similarly, other literature studies reported a bandgap of 3.21 eV from Hagenia abyssinica leaf extracts [31], 3.8 eV from Hibiscus sabdariffa flower extract [32], and 3.3 eV from Cnidoscolus aconitifolius aqueous leaf extracts [33]. Such differences of bandgap variations could emanate from several factors, ranging from the material particle size and surface roughness to the effect of lattice strain among the ZnO NPs formed from different plant extracts [34].…”
Section: Characterization Of Tm@zno/tmc Nc Hydrogelmentioning
confidence: 83%
“…The hydrodynamic size of TM@ZnO/TMC NC (Figure 1f) determined using dynamic light scattering (DLS) shows the particle diameter with an average size of 57.75 ± 19.18 nm for the aqueous preparation, which is a bit larger compared to the size distribution obtained from FESEM (Figure 1e). The increase was largely due to the deposition of hydrate layers on ZnO-NPs polymer surface [32].…”
Section: Characterization Of Tm@zno/tmc Nc Hydrogelmentioning
confidence: 99%
“…These ions build up inside the microbial cells, where they may potentially have a more deadly effect by generating free radicals and oxidative stress 24 . According to published studies, the synergistic interaction between nanoparticles and the organic compounds in cell walls is the primary cause of nanocomposite increased antimicrobial efficiency 60 , 87 , 88 . Any nanoparticle's antimicrobial activity targets cell division and the respiratory chain, which ultimately results in cell death and strengthens the antimicrobial effect 88 .…”
Section: Resultsmentioning
confidence: 99%
“…According to published studies, the synergistic interaction between nanoparticles and the organic compounds in cell walls is the primary cause of nanocomposite increased antimicrobial efficiency 60 , 87 , 88 . Any nanoparticle's antimicrobial activity targets cell division and the respiratory chain, which ultimately results in cell death and strengthens the antimicrobial effect 88 . A microbial cell's walls and membrane serve the important function of protecting the microbe from medicinal products, such as nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…The green synthesis of AgNPs via biological methods offers numerous benefits over physical and chemical synthesis since these methods use hazardous materials, have high equipment costs, and generate toxic compounds, while biological synthesis is simple, inexpensive, non-toxic, and environmentally friendly [26]. Due to the availability of several plants and their straightforward and secure application, plant-mediated synthesis of Ag-NPs is an extensively used approach for the biofabrication of AgNPs [27,28].…”
Section: Introductionmentioning
confidence: 99%